Legal Grounds III: Reproductive and Sexual Rights in Sub-Saharan African Courts - Godfrey Dalitso Kangaude (Pretoria University Law Press (PULP), 2017)
Legal Grounds III: Reproductive and Sexual Rights in Sub-Saharan African Courts is a joint publication of the International Reproductive and Sexual Health Law Program of the University of Toronto, Canada; the Centre for Human Rights, Faculty of Law, at the University of Pretoria, South Africa; and the Center for Reproductive Rights, New York. It is the expanded third volume in a series originally conceived by Kibrom Isaak, LL.M., a graduate of the International Reproductive and Sexual Health Law Program, who organised and wrote the prototype, and drafted most of the first two volumes. The editors of Legal Grounds III are tremendously grateful to all those who have supported us to produce this book. The planning and execution would not have been possible without a grant from the Ford Foundation. African publication and dissemination were generously supported, through the Centre for Human Rights, by The Open Society Foundations.